Perception of the problem of urban congestion by the citizens of Łódź - Łukasiewicz, Robert (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents' Perspective, 2024)
The chapter: "Perception of Urban Congestion by Residents of Łódź," addresses a crucial issue in the daily functioning of urban areas, namely congestion in transportation networks. The main objective of the chapter is to characterize the adverse phenomenon of congestion and examine how it is perceived by individuals moving within the city of Łódź. The study also aimed to identify the key factors influencing mobility within the city. Identifying ways to mitigate traffic congestion in cities, considering the analysis of its main causes, can serve as a basis for developing improvement plans and inspire initiatives aimed at optimizing the entire transportation system.To achieve the research objective, a quantitative study was conducted using a survey questionnaire, with a total of 120 responses collected. Among the most frequently mentioned causes of traffic congestion, respondents highlighted long-term and poorly organized roadworks. Interestingly, half of the respondents did not pay attention to the issue of single-occupancy car travel. The main consequences of traffic congestion, as identified by the survey participants, include time losses and, from an economic perspective, a decrease in interest in living in the city and unfavorable conditions for business development. The most common demands for improving traffic flow include the construction of infrastructure combined with Intelligent Transportation Systems. The study results reveal a greater inclination towards using individual transportation compared to collective transportation methods.